2021
DOI: 10.1029/2020jd033918
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Large‐Scale Circulation Patterns on Compound Dry and Hot Events in China

Abstract: Compound weather and climate extremes, such as compound dry and hot events (CDHEs), have been shown to be among the most disastrous hazards to the economic and social development across the globe (Y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 92 publications
(204 reference statements)
1
16
0
1
Order By: Relevance
“…Similarly, variations in the mean magnitude of CDHEs in community 6, located in the southern regions of SWC, are significantly correlated with the compounding effect of AMO and PDO, and AMO also dominates in positively modulating variations in the mean magnitude of community 6. Previous studies [23] have shown that the warm AMO phase tends to increase the frequency of CDHEs in northern China and the southern regions of SWC, and AMO is significantly and positively correlated with temperature in most of these regions. When AMO is in the warm phase, the warming of the northern China and the southern regions of SWC may lead to a high magnitude of CDHEs; this also explains the positive modulation of AMO in the frequency and magnitude of CDHEs in communities located in the northern China and the southern regions of SWC.…”
Section: The Propagation Extent and Driving Factors Of Cdhesmentioning
confidence: 78%
See 3 more Smart Citations
“…Similarly, variations in the mean magnitude of CDHEs in community 6, located in the southern regions of SWC, are significantly correlated with the compounding effect of AMO and PDO, and AMO also dominates in positively modulating variations in the mean magnitude of community 6. Previous studies [23] have shown that the warm AMO phase tends to increase the frequency of CDHEs in northern China and the southern regions of SWC, and AMO is significantly and positively correlated with temperature in most of these regions. When AMO is in the warm phase, the warming of the northern China and the southern regions of SWC may lead to a high magnitude of CDHEs; this also explains the positive modulation of AMO in the frequency and magnitude of CDHEs in communities located in the northern China and the southern regions of SWC.…”
Section: The Propagation Extent and Driving Factors Of Cdhesmentioning
confidence: 78%
“…AMO and PDO have been proven to influence the formation of CDHEs in China [23,28]. In this study, we correlate a temporal series of the mean frequency and mean magnitude within different communities with a temporal series of AMO and PDO indexes during JJA, aiming to explore the driving factors of CDHEs in different regions of China.…”
Section: The Propagation Extent and Driving Factors Of Cdhesmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal patterns of atmospheric circulation could also result in changes in extreme climate events (Berton et al., 2017; Shimizu et al., 2017; Wang et al., 2017). For example, the occurrences of compound dry and hot events in summer over mainland China were associated with the large‐scale circulation patterns, including the Atlantic Multidecadal Oscillation, North Atlantic Oscillation, Pacific Decadal Oscillation, and El Niño–Southern Oscillation (Wu et al., 2021). The frequency of hot drought events in summer over northeast China showed a significant correlation with the Atlantic Multidecadal Oscillation (Li, He et al., 2020).…”
Section: Introductionmentioning
confidence: 99%